Why Should Scientists be on YouTube? It’s all About Bamboo, Oil and Ice Cream - Brennan, Eric B. (Frontiers in Communication, 2021)
Scientific information is a key ingredient needed to tackle global challenges like climate change, but to do this it must be communicated in ways that are accessible to diverse groups, and that go beyond traditional methods (peer-reviewed publications). For decades there have been calls for scientists to improve their communication skills — with each other and the public — but, this problem persists. During this time there have been astonishing changes in the visual communication tools available to scientists. I see video as the next step in this evolution. In this paper I highlight three major changes in the visual communication tools over the past 100 years, and use three memorable items — bamboo, oil and ice cream — and analogies and metaphors to explain why and how Do-it-Yourself (DIY) videos made by scientists, and shared on YouTube, can radically improve science communication and engagement. I also address practical questions for scientists to consider as they learn to make videos, and organize and manage them on YouTube. DIY videos are not a silver bullet that will automatically improve science communication, but they can help scientists to (1) reflect on and improve their communications skills, (2) tell stories about their research with interesting visuals that augment peer-reviewed papers, (3) efficiently connect with and inspire broad audiences including future scientists, (4) increase scientific literacy, and (5) reduce misinformation. Becoming a scientist videographer or “sciencetuber” can be an enjoyable, creative, worthwhile and fulfilling activity that can enhance many aspects of a scientist’s career.